Wearable assistance system for interacting with electronic devices in smart digital home. (19th May 2011) - Seo, Yong-Ho; Song, Eunjee; Choi, Jin; Yang, Hyun S.
In the near future, we will frequently interact with many electronic devices that will be arrayed around us in a smart digital home. Under such circumstances, excessive interactions with these devices may become burdensome. A wearable computer able to understand the context of human activity and communicate autonomously with the surrounding electronic devices might function as an assistant in the daily life of people living in smart homes, thus alleviating that potential burden of excessive manual electronic interactions. In this paper, we present a wearable computer that can interact both with users and with electronic devices. We also propose an Infrared Identification system that can automatically identify the device that a user wants to use. Utilising these interaction capabilities, the proposed wearable computer mediates between the user and surrounding devices while offering a more user-friendly interface.